Proteus Syndrome: Report of a Case with Developmental Glaucoma - Sarman, Zuleyha Sik (The Korean Ophthalmological Society, 2014)
The purpose of this study was to report developmental glaucoma and pseudopapilledema in a patient with Proteus syndrome. We defined the presence of developmental glaucoma, right pseudopapilledema and myopia in a 4.5-year-old patient with Proteus syndrome. Marked right hemihypertrophy, lipoma, macrodactyly, and asymmetry of the limbs were observed on systemic examination. A cavernoma was also detected in magnetic resonance imaging of the brain. The patient underwent bilateral goniotomy surgery due to glaucoma. The surgical outcomes were satisfactory in both eyes. In conclusions developmental glaucoma and pseudopapilledema might be associated with Proteus syndrome.